Analysis of the masticatory process of asthmatic children: Clinical and electromyographic research - da Cunha, Daniele Andrade; da Silva, Hilton Justino; Nascimento, Gerlane Karla Bezerra Oliveira; da Silva, Elthon Gomes Fernandes; da Cunha, Renata Andrade; Régis, Renata Milena Freire Lima; de Castro, Célia Maria Machado Barbosa (International Archives of Otorhinolaryngology, 2012)
Introduction: The prevalence of asthma has grown considerably in recent decades, but some studies have shown stabilization of this trend. The masticatory process of asthmatic children may be altered due to asthma-related anatomo-functional changes.Objective: The study objective was to determine the clinical and electromyographic characteristics of the masticatory process in asthmatic children and compare the electrical activities of their masseter and anterior temporal muscles (at rest and during maximal voluntary contraction and mastication) with those of non-asthmatic children.Method: Case study. Asthmatic and non-asthmatic groups, each consisting of 30 children of both sexes between 6 and 10 years of age, were evaluated. Mastication was evaluated clinically and electromyographically in all subjects. RESULTS: The masticatory process did not differ significantly between asthmatic and non-asthmatic children.Conclusion: Although the masticatory process did not differ significantly between asthmatic and non-asthmatic children, the masticatory process of asthmatic children may be altered because of anatomical changes of Asthma.
Keywords: asthma; mastication; electromyography; child; stomatognathic system